IMPORTANCE OF PSYCHOPHYSIOLOGICAL CHARACTERISTICS OF CANDIDATES IN DRIVER TRAINING - Shukurov Nuritdin Rakhimovich (Journal Park Publishing, 2024)
According to the results of the analysis of the professional training system of motor vehicle drivers, one of the ways to solve the high-level problem of traffic accidents is to pay necessary attention to the professional qualities of drivers during educational activities. The article talks about the role of psychophysiological characteristics of candidates in the process of training motor vehicle drivers.
Keywords: driver's license, traffic rules, tests, practical driving, transport, driver's candidate.